Optical properties of fully conjugated cyclo[n]thiophenes – An experimental and theoretical approach - Mena-Osteritz, Elena; Zhang, Fan; Götz, Günther; Reineker, Peter; Bäuerle, Peter (Beilstein Journal of Nanotechnology, 2011)
Optical properties of two series of fully conjugated cyclo[n]thiophenes were analyzed experimentally and theoretically. The absorption spectra reveal a shift to higher wavelengths with increasing size of the cycles, which can be successfully described by an excitonic approach based on a Frenkel exciton Hamiltonian. Furthermore, intriguing new bands in the absorption and fluorescence spectra of the smaller macrocycles disclose the dominance of their ring strain.
Keywords: conjugated macrocycles; Frenkel exciton model; oligothiophene; photophysical properties